2018
DOI: 10.1093/femsle/fny037
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas oryzae pv. oryzae type III effector PthXo3JXOV suppresses innate immunity, induces susceptibility and binds to multiple targets in rice

Abstract: Transcription activator-like (TAL) effectors encoded by tal genes were recognized as a key virulence strategy used by Xanthomonas oryzae pv. oryzae (Xoo) to cause bacterial leaf blight of rice. TAL effector PthXo3 is a major virulence factor identified in a Philippine Xoo strain PXO61, and it can induce the expression of susceptibility gene OsSWEET14 by binding to the effector-binding element (EBE) in the promoter region. In this study, pthXo3 homologous genes were also identified and isolated from Xoo Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As a model system of plant–pathogen interactions, TAL and non‐TAL effectors in rice– Xanthomonas interactions have received widespread attention (Niño‐Liu et al ., 2006). Previously studies have identified numerous TAL effectors in Xoo that act as virulence factors, including Avrxa5 (Bai et al ., 2000), AvrXa7 (Yang et al ., 2000), PthXo1 (Yang et al ., 2006), PthXo6 and PthXo7 (Sugio et al ., 2007), Tal5 (Streubel et al ., 2013), PthXo2 (Zhou et al ., 2015), TalB (Tran et al ., 2018), TalC (Doucouré et al ., 2018), and PthXo3JXOV (R. Li et al ., 2018). Although there are more than 28 TAL effectors in several Xoc strains (Wilkins et al ., 2015), they have not received sufficient attention like TAL effectors in Xoo strains.…”
Section: Introductionmentioning
confidence: 99%
“…As a model system of plant–pathogen interactions, TAL and non‐TAL effectors in rice– Xanthomonas interactions have received widespread attention (Niño‐Liu et al ., 2006). Previously studies have identified numerous TAL effectors in Xoo that act as virulence factors, including Avrxa5 (Bai et al ., 2000), AvrXa7 (Yang et al ., 2000), PthXo1 (Yang et al ., 2006), PthXo6 and PthXo7 (Sugio et al ., 2007), Tal5 (Streubel et al ., 2013), PthXo2 (Zhou et al ., 2015), TalB (Tran et al ., 2018), TalC (Doucouré et al ., 2018), and PthXo3JXOV (R. Li et al ., 2018). Although there are more than 28 TAL effectors in several Xoc strains (Wilkins et al ., 2015), they have not received sufficient attention like TAL effectors in Xoo strains.…”
Section: Introductionmentioning
confidence: 99%
“…The major bacteria causing leaf blight in rice is Xanthomonas oryzae pv. o ., a bacteria that can cause damage at any stage of the life cycle, resulting in a serious decline in the crop yield . One of the main diseases affecting tobacco plants in tropical and subtropical regions (tobacco wilt) is caused by Ralstonia solanacearum .…”
Section: Introductionmentioning
confidence: 99%
“…Several TAL effectors from Xoo have been reported to be major virulence factors that may activate the expression of susceptibility genes ( S ) during infection. The key virulence factor of the Xoo strain PXO99 A in rice is PthXo1 [17].…”
Section: Introductionmentioning
confidence: 99%